THE EFFECT OF SUBTOTAL NEPHRECTOMY PROCEDURE ON THE GLOMERULOSCLEROSIS INDEX - Peranawa, I Wayan Yoga Diva; Witari, Ni Putu Diah; Cahyawati, Putu Nita (Meditory : The Journal of Medical Laboratory, 2025)
Background:  Chronic kidney disease is one of the kidney disorders with a steadily increasing incidence rate.Objective: This study aims to determine the effect of subtotal nephrectomy on the renal glomerulosclerosis in Mus musculus L. at 7, 14, and 28 days post-operation. Methods: This true-experimental study with a randomized post-test-only control group design used 16 white mice divided into four treatment groups (SO, SN7, SN14, and SN28). Kidney specimens were stained using Hematoxylin-Eosin and imaged to assess the glomerulosclerosis index. The results were analyzed using one-way ANOVA.Results:  The findings showed that glomerulosclerosis could be observed as early as 7 days post-procedure. The highest score was found in the SN28 group (3.55 ± 0.129). A significant difference was observed between the SO and SN7, SN14, and SN28 groups (p 0.05). Significant differences were also found between the SN7 and SN14 and SN28 groups (p 0.05), while no significant difference was observed between the SN14 and SN28 groups.Conclusions: These results indicate that subtotal nephrectomy can induce glomerulosclerosis as early as day seven post-operation. The highest glomerulosclerosis index was observed on day 28, although statistically, it did not differ significantly from the index on day 14.